Occult prostate carcinoma with metastasis to the mandible presenting as numb chin syndrome - Upasana Sethi Ahuja; Devi Charan Shetty; Akshay Rathore; Manu Dhillon (Journal of Oral Biology and Craniofacial Research)
Prostate cancer is one of the leading causes of death due to malignancy in men. Occult malignancy presenting with no primary symptoms could be a challenge to the diagnostician. Metastasis of prostate carcinoma to the mandible is rare and usually presents with non-specific symptoms. Only 1% of oral cancers account for lesions which present as metastasis of other primary malignancies. We report a rare case of prostate carcinoma being diagnosed as metastasis to the mandible with the patient presenting with numb chin syndrome.